Tópicos de geometria plana com o software geogebra: proposta de sequências didáticas - Fiorotti, Luciana Bahiense (2014)
According to the reality of the schools that I have worked the teaching of plane geometry is deficient, causing students to forget certain facility settings and properties. A source that can (and should) be used is the proposal of the present dissertation: an educational software for the study of plane geometry. To be more explicit, we propose the use of the GeoGebra software, which is free, to show some topics of plane geometry. The idea is to bring the student to assimilate definitions and properties through geometric constructions, using didactic sequences in GeoGebra. These didactic sequences may be used in any term of high school, once the main goal of the project is to support students, regardless the series that they are attending. The first sequences are intended to show some features of the software and the other, geometric constructions and properties involved.